An ex vivo lung model to study bronchioles infected with Pseudomonas aeruginosa biofilms - Harrison, Freya; Diggle, Stephen P. (Society for General Microbiology, 2016)
A key aim in microbiology is to determine the genetic and phenotypic bases of bacterial virulence, persistence and antimicrobial resistance in chronic biofilm infections. This requires tractable, high-throughput models that reflect the physical and chemical environment encountered in specific infection contexts. Such models will increase the predictive power of microbiological experiments and provide platforms for enhanced testing of novel antibacterial or antivirulence therapies. We present an optimised ex vivo model of cystic fibrosis lung infection: ex vivo culture of pig bronchiolar tissue in artificial cystic fibrosis mucus. We focus on the formation of biofilms by Pseudomonas aeruginosa. We show highly repeatable and specific formation of biofilms that resemble clinical biofilms by a commonly-studied lab strain and ten cystic fibrosis isolates of this key opportunistic pathogen.